Discourse Competence in English E-Book “Contextual Teaching and Learning” for 9th Grade Students of Junior High School - Rosyida, Ulva Fatiya (Journal of English Teaching and Learning Issues, 2019)
Discourse competence is the main competence in Communicative Competence. In language teaching, the role of discourse is to achieve good communication. This study aims at describing the discourse competences in English e-book for students of Junior High School grade 9. The data was collected by using “documentation”. The spoken materials presented in section one for each unit was taken as the data. In analyzing the data, the method used here are Padan (identity) method with “referential” instrument and Agih (distributional) method. They were analyzed how the materials convey the components of discourse competence based on the model of communicative competence proposed by Celce-Murcia, et.al. From the analysis, it was found that the materials convey the components of discourse competence although there are no clear highlights showing each component.